Association of Plasma DPP4 Activity and Brain-Derived Neurotrophic Factor With Moderate to Severe Depressive Symptoms in Patients With Type 2 Diabetes: Results From a Cross-Sectional Study. Issue 4 (May 2020) - Zheng, Tianpeng; Ge, Bo; Qin, Linyuan; Chen, Bo; Tian, Li; Gao, Yun; Xiao, Liuping; Hu, Xueping; Pan, Haidong; Chen, Yujie
ABSTRACT: Objective: The objective of this study was to assess the association of plasma dipeptidyl peptidase-4 (DPP4) activity, brain-derived neurotrophic factor (BDNF), and the DPP4/BDNF ratio (DBR) with moderate to severe depressive symptoms in patients with type 2 diabetes mellitus. Increased DPP4 activity and decreased BDNF in peripheral circulation have been implicated in the pathophysiology of depression. Methods: We performed a cross-sectional study using data from 1535 patients with type 2 diabetes mellitus. The main outcome measures were plasma DPP4 activity, BDNF levels, DBR, inflammation markers, and oxidative stress parameters. Depressive symptoms were assessed using the nine-item Patient Health Questionnaire. Results: DPP4 activity and BDNF were negatively correlated in patients with and without moderate to severe depressive symptoms ( p < .001). Oxidative stress partially mediated the inverse correlation between DPP4 and BDNF. Nitrotyrosine, 8-iso-PGF2a, interleukin-6, C-reactive protein, and the nine-item Patient Health Questionnaire score increased significantly with rising quartiles of DBR. Patients in the highest quartile of DPP4 activity and DBR and lowest quartile of BDNF more often had moderate to severe depressive symptoms compared with those in the lowest quartile of DPP4 activity and DBR and the highest quartile of BDNF, respectively ( p < .05). The likelihood of having moderate to severe depressive symptoms increased more with higher DPP4 activity and lower BDNF. Conclusions: Our hypothesis-generating study demonstrates that oxidative stress might partially play a mediating role in the negative relationship between DPP4 activity and BDNF. DBR is positively related to moderate to severe depressive symptoms and thus might be used as a novel biological measure associated with depressive symptoms in patients with type 2 diabetes mellitus.